2013
DOI: 10.5588/ijtld.12.0426
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and 2-month culture conversion during anti-tuberculosis treatment

Abstract: SUMMARY OBJECTIVE To investigate risk factors for delayed sputum culture conversion to negative during anti-tuberculosis treatment, with an emphasis on smoking. DESIGN Nested case-control study of adults with non-cavitary, culture-confirmed pulmonary tuberculosis (TB) participating in an anti-tuberculosis treatment trial in Brazil. A case of delayed culture conversion was a patient who remained culture-positive after 2 months of treatment. Odds ratios with 95% confidence intervals were calculated. RESULTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
46
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 11 publications
8
46
0
3
Order By: Relevance
“…Our observations of more extensive lung disease, lung cavitation and positive sputum smears among current smokers and ex-smokers corroborate those reported in previous studies [16][17][18] and point to potentially enhanced secondary transmission risk [19]. In this study, both current smokers and ex-smokers were 1.5-2 times as likely to remain smear-positive and culture-positive after 2 months of treatment, closely parallel to the observation in a previous Brazilian case-control study that ever-smokers who smoked >20 cigarettes per day were also reported to be two-fold as likely to remain culture-positive after 2 months of treatment [20]. The slower bacteriological response raises concern over persistent transmission risk after the initiation of treatment, even for patients with initially fully drug-sensitive TB as included in the current study.…”
Section: Discussionsupporting
confidence: 74%
“…Our observations of more extensive lung disease, lung cavitation and positive sputum smears among current smokers and ex-smokers corroborate those reported in previous studies [16][17][18] and point to potentially enhanced secondary transmission risk [19]. In this study, both current smokers and ex-smokers were 1.5-2 times as likely to remain smear-positive and culture-positive after 2 months of treatment, closely parallel to the observation in a previous Brazilian case-control study that ever-smokers who smoked >20 cigarettes per day were also reported to be two-fold as likely to remain culture-positive after 2 months of treatment [20]. The slower bacteriological response raises concern over persistent transmission risk after the initiation of treatment, even for patients with initially fully drug-sensitive TB as included in the current study.…”
Section: Discussionsupporting
confidence: 74%
“…Mounting evidence from a number of countries in both the developed and developing worlds attests not only to the predisposing effect of smoking for the development of pulmonary TB [105][106][107][108][109][110][111][112], but also for more severe disease progression [113], decreased efficacy of antimicrobial chemotherapy [114], prolonged infectivity [115][116][117], recurrence of disease [118], poor outcomes of multidrug-resistant TB [119] and possibly impaired post-treatment lung function [120].…”
Section: Tuberculosismentioning
confidence: 99%
“…In the case of the former, however, differences in cavitation, which is largely immune-mediated, may be difficult to detect due to smoking-related pulmonary immune dysfunction; irrespective of this caveat, a previous study involving 13,088 cases of pulmonary TB has, however, documented more severe cavitary disease in smokers 6 . With respect to culture conversion, delayed sputum conversion in smokers has also been reported in several studies [27][28][29] . Follow-up studies may also identify the relative contributions of infection and smoking to the observed alterations in vitamin C status.…”
Section: Discussionmentioning
confidence: 61%